2003
DOI: 10.1074/jbc.m307491200
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of the Two Zinc Binding Sites in DnaJ

Abstract: All type I DnaJ (Hsp40) homologues share the presence of two highly conserved zinc centers. To elucidate their function, we constructed DnaJ mutants that separately replaced cysteines of either zinc center I or zinc center II with serine residues. We found that in the absence of zinc center I, the autonomous, DnaK-independent chaperone activity of DnaJ is dramatically reduced. Surprisingly, this only slightly impaired the in vivo function of DnaJ, and its ability to function as a co-chaperone in the DnaK/DnaJ/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
87
1
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 41 publications
7
87
1
5
Order By: Relevance
“…2B) is important for interaction of DnaJ with another chaperone protein, DnaK (44,45). Substitution of any cysteine residue by serine in this domain reduced DnaK-dependent chaperone activity (44). Similar results were obtained for Ydj1, a close homologue of DnaJ in yeast (46).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…2B) is important for interaction of DnaJ with another chaperone protein, DnaK (44,45). Substitution of any cysteine residue by serine in this domain reduced DnaK-dependent chaperone activity (44). Similar results were obtained for Ydj1, a close homologue of DnaJ in yeast (46).…”
Section: Resultssupporting
confidence: 72%
“…The second zinc-binding domain (Zn2 in Fig. 2B) is important for interaction of DnaJ with another chaperone protein, DnaK (44,45). Substitution of any cysteine residue by serine in this domain reduced DnaK-dependent chaperone activity (44).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(17). It has been reported that zinc finger 1 is necessary for the autonomous chaperone activity in cooperation with the C-terminal domain (5,7,13), and zinc finger 2 together with the J domain are absolutely essential for the interaction with DnaK (13). Thus, we localized the zinc finger domain in such a way to make zinc finger 1 toward C-terminal domain and the zinc finger 2 close to the J domain, for fitting the different functions of the two zinc fingers.…”
Section: Saxs Parameters-as Shown Inmentioning
confidence: 99%
“…In addition to the DnaK-dependent co-chaperone activity described above, DnaJ also exerts autonomous DnaK-independent chaperone activity (9,12,13), which is characterized by its ability to bind with unfolded proteins and prevent them from irreversible aggregation (10,11). Moreover, DnaJ has been found to have thiol-disulfide oxidoreductase activity but little, if any, isomerase activity (14).…”
mentioning
confidence: 99%